Deformable Surface Reconstruction Through Optimization-Based Techniques - Shamoushaki, Seyed Jafar Hosseini (2017)
PhD thesis in Electrical and Computer Engineering, the specialization branch of Automation and Robotics submitted to the Faculty of Science and Technology of the University of Coimbra